Peningkatan Peran Perempuan Dalam Ketahanan Pangan Berbasis Kearifan Lokal dan Pemanfaatan Sumber Daya di Desa Tolomato - Dama, Lilan; Sulistijowati, Rieny; Bagtayan, Nazwa (Universitas Negeri Gorontalo, 2025)
Food security is a strategic issue in rural areas as it relates to the availability, accessibility, and sustainability of food based on local potential. Women play a central role in maintaining food security, both as household managers and as village economic actors. This study refers to the literature on local wisdom, value-added products, and Rogers diffusion of innovation theory to explain how simple innovations can be adopted by communities. The implementation method applied a community engagement approach through the Thematic Community Service Program of Universitas Negeri Gorontalo, which consisted of four stages: preparation, implementation, evaluation, and follow-up. The activities focused on training women in processing papaya into sambal papaya as a locally based food product with market value, along with introducing digital marketing as a modern strategy to expand market access. The results indicate an improvement in women’s technical skills in processing papaya into innovative products, increased awareness of the economic potential of local food resources, and new knowledge of utilizing social media for marketing purposes. The active participation and enthusiasm of the community highlight that strengthening women’s capacity through local resource utilization can encourage economic independence while enhancing village food security. In conclusion, women’s empowerment based on local wisdom and the integration of digital technology serves as an effective strategy to achieve sustainable food security in Tolomato Village.